2004
DOI: 10.1002/jcp.20004
|View full text |Cite
|
Sign up to set email alerts
|

Initial interactions in electromagnetic field‐induced biosynthesis

Abstract: Low frequency electromagnetic (EM) fields induce gene expression, and recent insights into physical interactions of EM fields with model systems suggest a mechanism that could initiate this process. The consistently low thresholds at which EM fields stimulate biological processes indicate that they require little energy. Since it has been shown that such weak fields accelerate electron transfer reactions, they could stimulate transcription by interacting with electrons in DNA to destabilize the H-bonds holding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 39 publications
1
61
0
2
Order By: Relevance
“…The low EMF energy can move electrons, cause small changes in charge distribution and release the large hydration energy tied up in protein and DNA structures [3]. Electrons have been shown to move in DNA at great speed [50], and we have suggested that RF and ELF fields initiate the stress response by directly interacting and accelerating electrons moving within DNA [52,53].…”
Section: Emf-dna Interaction Mechanisms: Electron Transfermentioning
confidence: 97%
“…The low EMF energy can move electrons, cause small changes in charge distribution and release the large hydration energy tied up in protein and DNA structures [3]. Electrons have been shown to move in DNA at great speed [50], and we have suggested that RF and ELF fields initiate the stress response by directly interacting and accelerating electrons moving within DNA [52,53].…”
Section: Emf-dna Interaction Mechanisms: Electron Transfermentioning
confidence: 97%
“…and interaction of electromagnetic wave with DNA and gene promoters [27]. The data presented in this article show the influence of electromagnetic irradiation on the nuclear chromatin structure.…”
Section: Figure 12mentioning
confidence: 59%
“…The EMF may interact directly with electrons in DNA and the electron transfer would result in gene expression [19]. Because of the low energy required, interaction with electrons in H-bonds may be the initial perturbation that leads double stranded DNA to come apart and begin the complex process of transcription to messenger RNA [20]. This model is detailed in [21].…”
Section: The Action Of Emf On Intracellular Regulatory Systemsmentioning
confidence: 99%
“…Th e medical applications of EMFs are reviewed by Rosch PJ, Markov MS; Andrä W, Nowak H; Markov MS [5][6][7]. Some of theoretical models proposed to explain the basic phenomena associated with cell exposure to EMF are presented in review articles [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Now some new data are emerging and the approaches to the problem of the action of electromagnetic factors on cells are changing in accordance to the new developments in biology as a whole.…”
Section: Introductionmentioning
confidence: 99%